2017
DOI: 10.1080/14760584.2018.1411195
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of human papilloma virus vaccination in low and middle income countries: a systematic review of literature

Abstract: Low and middle income countries (LMICs) bear more than 50% of the current cervical cancer burden over the last decade with linkages to lack of HPV vaccination, high levels of poverty, illiteracy and nonexistent or poor screening programs. Governments of LMICs need enough convincing evidence that HPV vaccination will be more cost-effective in reducing the scourge of cervical cancer. Area covered: A systematic review to identify suitable studies from MEDLINE(via PubMed), EMBASE and Electronic search through GOOG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Our finding that 2-dose vaccination with this novel 2vHPV is very cost effective and has implications for CC control in both China and other resource-limited countries. Despite the heterogeneity of vaccination strategies and HPV prevalence, numerous studies 31,32 have shown that introducing HPV vaccines is cost effective. Especially in some resource-limited countries such as South Africa, Malaysia and India, introducing 2vHPV vaccines without screening is cost effective because of the high rates of CC in those countries.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that 2-dose vaccination with this novel 2vHPV is very cost effective and has implications for CC control in both China and other resource-limited countries. Despite the heterogeneity of vaccination strategies and HPV prevalence, numerous studies 31,32 have shown that introducing HPV vaccines is cost effective. Especially in some resource-limited countries such as South Africa, Malaysia and India, introducing 2vHPV vaccines without screening is cost effective because of the high rates of CC in those countries.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis reported that the HPV vaccine program was economical in resource-constrained settings. 24 There was a media outcry in 2012 after a few deaths were reported in a cervical cancer trial that was conducted in India. 2,25,26 This led to an adverse public opinion in India against the HPV vaccine.…”
Section: Challenges To Implementation Of Hpv Vaccine In India and Solutionsmentioning
confidence: 99%
“…Health economics: The need for cost-effectiveness in public health services can never be overlooked, especially by the policy makers. 20 It may interest to note that there could economic returns from HPV vaccination. A systematic review study from Hong Kong reported HPV vaccination was considered to be cost-effective or costsaving, 21 though another systematic review highlighted that variations in the service strategies have implications on cost-effectiveness.…”
Section: Public Health Education Significance: Two Points Of Notementioning
confidence: 99%
“…3 Even at the public health policy making level, the concept of belief is captured in the suggestion that "Governments need convincing evidence that HPV vaccination will be more cost-effective in reducing the scourge of cervical cancer". 20 Therefore, 'belief' is still an issue to address even in the public health ministry.…”
Section: Public Health Education Significance: Two Points Of Notementioning
confidence: 99%